MECHANICALL METHODS RELEASING STUCK DRILLING TOOLS (OVERVIEW) - Левчук, Катерина Григорівна; Мойсишин, Василь Михайлович; Рис, Віталій Васильович; Гураль, Інеса Михайлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The authors reviewed the types of sticks, the physical nature and the prevention of the picking up of the drill tool. The place of trapping of drilling systems among accidents and complications during drilling of oil and gas wells is found out. We have done a bibliographic review of the methods to eliminate drill string, as well as recommendations for choosing existing methods to effectively deal with accidents.